Quantitative Prostate MRI Analysis Following Fluvastatin Therapy for Localized Prostate Cancer - A Pilot Study. Issue 4 (November 2021) - Avery, Allan; Sussman, Marshall; Longo, Joseph; Menezes, Ravi J.; Hamilton, Robert J.; der Kwast, Theodorus H. van; Fleshner, Neil E.; Penn, Linda Z.; Ghai, Sangeet
Purpose: To assess the role of multi-parametric MRI (mpMRI) in assessment of tumor response to fluvastatin administered prior to radical prostatectomy. Methods: Men with MRI-visible, clinically significant prostate cancer and due to be treated with radical prostatectomy were prospectively enrolled. mpMRI was performed at baseline and following 6-7 week of neoadjuvant oral statin therapy (40 mg fluvastatin, twice daily), prior to prostatectomy. MRI assessment included tumor size, T2 relaxation time, ADC value, K-trans (volume transfer constant), Kep (reflux constant), and Ve (fractional volume) parameters at the 2 time points. Initial prostate needle biopsy cores, prior to starting oral statin therapy, corresponding to site of tumor on radical prostatectomy specimens were selected for analysis. The effect of fluvastatin on tumor proliferation (marker Ki67) and on tumor cell apoptosis (marker cleaved Caspase-3, CC3) were analyzed and correlated with MRI findings. Results: Nine men with paired MRI studies were included in the study. Binary histopathological data was available for 6 of the participants. No significant change in tumor size ( P = 0.898), T2 relaxation time ( P = 0.213), ADC value ( P = 0.455), K-trans ( P = 0.613), Kep ( P = 0.547) or Ve ( P = 0.883) between the time of biopsy and prostatectomy were observed. No significant change in tumor proliferation (%Ki67-positive cells, P = 0.766) was observed by immunohistochemistry analysis. However, there was a significant increase in tumor cell apoptosis (%CC3-positive cells, P = 0.047). Conclusion: mpMRI techniques may not be sufficiently sensitive to detect the types (or magnitude) of tumor cell changes observed following 6-7 weeks of fluvastatin therapy for prostate cancer.